The problem of artificial intelligence in the context of existential ontology - Alaverdyan, Nelli (Bulletin of Yerevan University E: Philosophy, Psychology, 2025)
In today’s virtual and increasingly digitalized world, the questions surrounding the relationship between the development of artificial intelligence and the existential ontology of the human being have acquired new theoretical and practical significance. These issues require focused philosophical and socio-cultural reflection.Taking this reality into account and addressing the challenges facing contemporary society, the article places special emphasis on the fundamental questions concerning the nature, development, and functions of artificial intelligence, as well as the problems and potential risks it poses. Attention is also given to the prospects for effective human–AI interaction and the potential of human–machine systems to contribute to solving real societal issues.The core issue lies in the fact that the increasing penetration of artificial intelligence into nearly all spheres of life—its growing role in the digital economy, business, and other domains—as well as the emergence of virtual reality and the post-human era, demand a rethinking of the place and role of cutting-edge technologies in human life.Furthermore, the interest in artificial intelligence is driven not only by the modern human’s attraction to technological innovations that aim to improve socio-economic life, but also by the fact that AI exhibits playful dimensions and is tied to questions concerning the organization of leisure and entertainment in consumer society.